Characterization and Pathological Analysis of a Virulent Edwardsiella anguillarum Strain Isolated From Nile Tilapia (Oreochromis niloticus) in Korea - Oh, Woo Taek; Jun, Jin Woo; Kim, Hyoun Joong; Giri, Sib Sankar; Yun, Saekil; Kim, Sang Guen; Kim, Sang Wha; Kang, Jeong Woo; Han, Se Jin; Kwon, Jun; Park, Se Chang (Frontiers in Veterinary Science, 2020)
Edwardsiella species are one of the top causative pathogens of mortality in various fisheries worldwide. Their role in zoonotic infections and increase in antibiotic-resistance has raised concerns and interests in many research fields. Similar to the studies investigating human clinical cases, there has been an increase in research examining the potential pathogenic role of the bacterium in aquaculture. Within the Edwardsiella family, E. anguillarum was lastest group to be differentiated from the E. tarda group, and many studies focusing on the virulence of this species have since ensued. In Korea, only E. tarda infections have been reported in aquaculture industries, and there have been no reports on economic losses incurred owing to E. anguillarum infection. There has been a recent report investigating the pathogenicity and pathological changes caused by E. anguillarum infection in a tilapia farm located in the USA. To the best of our knowledge, as ours is the first report of E. anguillarum infection in a Nile tilapia (Oreochromis niloticus) farm located in an Asian country, the pathogenicity of the bacterial strain was histopathologically compared to that of the past studies. As tilapia is one of the most globally consumed fish species, particularly throughout Asia, Europe, and America, an epidemiological study regarding the disease distribution is necessary for the control and prevention of the disease. Here, we report the first mass mortality case caused by E. anguillarum infection in a Nile tilapia farm located in Korea; the bacterial strain responsible was isolated, characterized, and pathologically analyzed.